Новые находки нюрнбергских жетонов в Белгород-Днестровском - Кокоржицкая, Т.Н.; Корпусова, И.В. (Материалы по археологии Северного Причерноморья, 2009)
Reckoning counters (jetons) were intended to be used in computation in European equivalent of abacus. These coin-like objects most commonly were usually made from brass or cooper. In the late 14th century the German town Nuremberg began making casting counters and by the end century was the main source of supply for everyone requiring counters in most European countries. In Nuremberg this production was controlled by «spengler’s» guild. The jetons from period before 1500 are known as the «anonymous». Later Nuremberg guildhouses signed or initialed their products. In 1912 during archeological Research in Akkerman (Belgorod-Dnestrovsky) were found two reckoning counters with names of Hanns Krauwinckel and Adam Vogel. Last years the archeologists have discovered there another two jetons. First of them is rare and belong to «anonymous» type. The second was made in the guildhouse of Hanns Krauwinckel II.